(3bQH GdESfGOs - (3GdMejQj, Gdbej, CHh GdYHGS, YHO Gddg Hf LYaQ Hf GdMSjf Hf eGdc, (B310 (3g`s ((3MSjf GdCcQGOs)
(3ChdgG (B:s
(3eMeO Hf YHO Gddg Hf LYaQ GdMejQj Yf CHjg(B... (3cGf Ydj jbhd aj OYGFg hgh SGLO(B: (3Gddge Efj CYhP Hc Cf JHJdjfj(B...s
(3BNQgG (B:s
(3hJfRd GdeGA aYdjgG ZSd Ce dG? bGd(B: (3fYe, EPG LGAJ GdTghI hCfRdJ GdeGA hLH YdjgG GdZSd(B. (3BNQ GdLRA GdKGdK(B...s
(3ebGHdI (B: (3QLH, (B1087(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B449s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B449s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs